Disaggregated trade flows and the missing globalization puzzle - Boriss Siliverstovs; Dieter Schumacher (ETH Zurich, KOF Swiss Economic Institute, 2008)
This study analyzes the stability of the distance coefficient values over time in the generalized gravity equation of Bergstrand (1989) using both aggregate and disaggregated trade flows among 22 OECD countries recorded for the sample period covering 1970 until 2000. We estimate the gravity equation both in its traditional form as well as by taking into account multilateral resistance as suggested in Baier and Bergstrand (2007). First of all, we find that the missing globalization puzzle, typically observed in empirical gravity models for aggregate trade flows, largely disappears when one estimates a gravity model using disaggregated trade data at the level of individual industries. Secondly, we document that accounting for multilateral price resistance alone can provide some evidence against the missing globalization puzzle. At the same time, the results obtained for a traditional specification of the gravity equation emphasizing the importance of disaggregated trade flows in explaining the distance puzzle remain largely intact. We also illustrate how the aggregation bias could have contributed to a typical finding of a non-declining trade-deterring role of distance in the existing literature.
Keywords: F12; 330; Gravity model; missing globalization puzzle; distance coefficient; multilateral resistance; Gravitationsmodell; Entfernung; Internationale Wirtschaftsbeziehungen; Theorie; OECD-Staaten